A Phase I study evaluating the safety and immunogenicity of MVA85A, a candidate TB vaccine, in HIV-infected adults. Issue 2 (14th November 2011) - Minassian, Angela M; Rowland, Rosalind; Beveridge, Natalie E R; Poulton, Ian D; Satti, Iman; Harris, Stephanie; Poyntz, Hazel; Hamill, Matthew; Griffiths, Kristin; Sander, Clare R; Ambrozak, David R; Price, David A; et al.
Abstract : Objectives: Control of the tuberculosis (TB) epidemic is a global health priority and one that is likely to be achieved only through vaccination. The critical overlap with the HIV epidemic requires any effective TB vaccine regimen to be safe in individuals who are infected with HIV. The objectives of this clinical trial were to evaluate the safety and immunogenicity of a leading candidate TB vaccine, MVA85A, in healthy, HIV-infected adults. Design: This was an open-label Phase I trial, performed in 20 healthy HIV-infected, antiretroviral-naïve subjects. Two different doses of MVA85A were each evaluated as a single immunisation in 10 subjects, with 24 weeks of follow-up. The safety of MVA85A was assessed by clinical and laboratory markers, including regular CD4 counts and HIV RNA load measurements. Vaccine immunogenicity was assessed by ex vivo interferon γ (IFN-γ) ELISpot assays and flow-cytometric analysis. Results: MVA85A was safe in subjects with HIV infection, with an adverse-event profile comparable with historical data from previous trials in HIV-uninfected subjects. There were no clinically significant vaccine-related changes in CD4 count or HIV RNA load in any subjects, and no evidence from qPCR analyses to indicate that MVA85A vaccination leads to widespread preferential infection of vaccine-induced CD4 T cell populations. Both doses of MVA85A induced an antigen-specific IFN-γ response that was durable for 24 weeks, although of a lesser magnitude compared with historical data from HIV-uninfected subjects. The functional quality of the vaccine-induced T cell response in HIV-infected subjects was remarkably comparable with that observed in healthy HIV-uninfected controls, but less durable. Conclusion: MVA85A is safe and immunogenic in healthy adults infected with HIV. Further safety and efficacy evaluation of this candidate vaccine in TB- and HIV-endemic areas is merited.